[Port-of-Spain Harbour] - (:unkn) unknown (My University, 2009)
A picture of the Port-of-Spain Harbour. You can see boats docked and a man looking out at the ocean. Affixed to this card are a Trinidad and Tobago ten cent stamp, featuring the General Hospital, San Fernando and two cent stamp highlighting Queen's Hall. Postcard number C9490.
Colour: Coloured; Style: Landscape; Other: Unbordered; Divided.
Keywords: Trinidad and Tobago; Postcards; Habors--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Docks--Trinidad and Tobago; Piers--Trinidad and Tobago; Wharves--Trinidad and Tobago; Barrels--Trinidad and Tobago; Bicycles--Trinidad and Tobago; Men--Trinidad and Tobago; Hats--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Lumber--Trinidad and Tobago; Seas--Trinidad and Tobago; Imports--Trinidad and Tobago; [1962]; Jetties--Trinidad and Tobago